EFEKTIVITAS KOMPRES HANGAT TERHADAP PENURUNAN NYERI PADA PENDERITA GOUT ARTHRITIS DI WILAYAH KERJA PUSKESMAS PULOSARI KABUPATEN PANDEGLANG BANTEN TAHUN 2021 - Eneng Aminah; Milla Evelianti Saputri; Tommy J F Wowor (Universitas Sam Ratulangi, 2022)
Background: metabolic system characterized by acute inflammation caused by the formation of urate crystallization in the joints, signs and symptoms that are usually felt are pain in the joints and swelling can occur. Control it by non-pharmacological methods with warm compresses. Aim: This study aims to determine the effectiveness of warm compresses on reducing pain in patients with gout arthritis. Methods: The research design used a Quasi Experimental pre-test and post-test one group design. The sample in this study used a total sample of 44 respondents. This research instrument uses NRS (Numerical Rating Scale) and colored paper to show the level of pain according to the NRS. Data were analyzed by Wilcoxon test. Results: The results of this study indicate that there is a significant difference in pain reduction in patients with gout arthritis before and after giving warm compresses with the result value of Asymp Sign = 0.000 or (p value <0.005) stating that Ha is accepted and Ho is rejected, meaning that there is an effect or effective in reducing pain in patients with gouty arthritis. Conclusions: Giving warm compresses is effective in reducing pain in patients with gout arthritis, this intervention can be done independently by the patient.Keywords: Gout arthritis; Warm Compress; Pain